The role of risk and usefulness in determining an adoption of Islamic mobile banking services: The case of Malaysia - Mohd Thas Thaker, Mohamed Asmy; Sharin, Raisudin; Mohd Sa’adon, Amir Hariri; Syed Salim, Syarifah Mardhiah; Allah Pitchay, Anwar; Mohd Thas Thaker, Hassanudin (2017)
This study is designed to identify the factors that are influencing adoption of Islamic mobile banking services in Malaysia. The primary data are collected from the survey administered to existing customers of Islamic banking and services in the Klang Valley and the analysis is conducted using Partial Least Squares (PLS). This study has verified the factors of risk and usefulness are found to have a positive impact on the adoption of Islamic mobile banking services. The findings of this study can be used to develop a specific framework or policy and to plan appropriate intervention strategies to increase its capacity in nurturing adoption of Islamic mobile banking services.